2023
DOI: 10.5812/archcid-134837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of β-lactamases and Molecular Typing of Pseudomonas aeruginosa Clinical Strains Isolated from Hospitalized Children in Tehran, Iran

Abstract: Background: The opportunistic human pathogen, Pseudomonas aeruginosa, is a critical cause of nosocomial infection with high morbidity and mortality rate. Eradication of P. aeruginosa has been troublesome due to its high capacity to develop strong multidrug resistance (MDR). Objectives: The purposes of this study were to define the pattern of antimicrobial sensitivity, typing, and prevalence of metallo-β-lactamase (MBL) and detect the oprD, blaCTX-M, blaSHV, blaTEM, blaIMP, blaNDM, and blaVIM among clinical iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
3
0
0
Order By: Relevance
“…Co-carriage of blaTEM and blaCTX-M was found in 23% of isolates carrying ESBL genes. In line with our results, Goudarzi et al from Iran [ 51 ], Nasser et al from Yemen [ 52 ], and Ejaz from Pakistan [ 53 ] reported that blaCTX-M was the more prevalent ESBL gene than TEM and SHV types among P. aeruginosa . In contrast to our results, blaTEM was the most detected in West Iran among P. aeruginosa isolates from coronavirus disease-19 patients [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…Co-carriage of blaTEM and blaCTX-M was found in 23% of isolates carrying ESBL genes. In line with our results, Goudarzi et al from Iran [ 51 ], Nasser et al from Yemen [ 52 ], and Ejaz from Pakistan [ 53 ] reported that blaCTX-M was the more prevalent ESBL gene than TEM and SHV types among P. aeruginosa . In contrast to our results, blaTEM was the most detected in West Iran among P. aeruginosa isolates from coronavirus disease-19 patients [ 54 ].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of carbapenem resistance in the present study was (62/163 = 38%), similar to the findings of Saha et al [31]. In another study, Goudarzi et al [32] reported that carbapenemresistant P. aeruginosa was 20% (n = 20), and among them, only 25% (n = 4) were MBL producers. Therefore, IPM-resistant P. aeruginosa can produce MBLs, making them resistant to multiple antibiotics and posing a significant public health threat.…”
Section: Discussionsupporting
confidence: 91%
“…Co-carriage of blaTEM and blaCTX-M was found in 23% of isolates carrying ESBL genes. In line with our results, Goudarzi et al from Iran51 , Nasser et al from Yemen 52 and Ejaz from Pakistan 53 reported that blaCTX-M was the most prevalent ESBL gene than TEM and SHV types. In contrast to our results, blaTEM was the most detected in West of Iran among P.…”
supporting
confidence: 92%